Multiple Unite Pellet Systems (MUPS) as Drug Delivery model - Majeed, Saad M.; Al-Shaheen, Mohammed K.; Al-Zidan, Radhwan Nidal; Mahmood, Sameer M. (Journal of Drug Delivery and Therapeutics, 2020)
Multiparticulate drug delivery systems are mainly oral dosage form, consist of small discrete units that exhibit different characteristics especially in release pattern and drug bioavailability. These systems are represented by granules, pellets, microspheres, microcapsules, and minitablets. Pellets offer high flexibility in the design, formulation, and development of oral dosage forms such as sachet, suspension, capsule, and tablet. Multiparticulate tablets manufactured by compaction of multiple unite pellets is one of the latest and, yet, challenging technologies. Multiparticulate tablets combine the benefits of both a tablet and a pellet-filled capsule in one dosage form but their manufacturing experience many difficulties. The oral multiparticulate products consist of polymer-coated subunits or pellets, which are embedded in an inert excipients’ matrix, formulated to overcome the difficulty in administering capsules and improve the physicochemical stability of suspension and offer predictable release and uniform distribution in the gastro-intestinal tract compared to the plain tablet. This review discusses the advantages and drawbacks of MUPS, the properties of an ideal MUPS, various pharmaceutical applications of MUPS, the challenges and key variables that to be considered in the tableting process for successful production of MUPSKeywords: MUPS®, Pellets, Multiparticulate tablets.